Germination of oospores of Sclerospora graminicola - and H.R. DAVE, C. LUKOSE (Indian Phytopathology, 2002)
The germination of oospores of Sclerospora graminicola (Sacc.) Schroet, causing downy mildew disease of pearl millet has been a subject of controversy. The oospores have been reported to germinate by germ tubes, germ sporangia, sporangiophores, the extrusion of small multinucleate bodies and the formation of vesicles. In a recent study on oospore germination at ICRISAT, the oospores were observed to germinate by single germ tube only. This area of research needs more investigations in view of the inconsistent results obtained by the earlier workers. Therefore, the present study was conducted to examine the success of germination and the variabilities associated with this process.